Small interfering RNAs generated from the terminal panhandle structure of negative-strand RNA virus promote viral infection. - Wan Zhao; Qiong Li; Mengqi Sun; Lan Luo; Xiaoming Zhang; Feng Cui (PLoS Pathogens)
Virus-derived small interfering RNAs (vsiRNAs) have been widely recognized to play an antiviral immunity role. However, it is unclear whether vsiRNAs can also play a positive role in viral infection. Here, we characterized three highly abundant vsiRNAs mapped to the genomic termini of rice stripe virus (RSV), a negative-strand RNA virus transmitted by insect vectors. The three vsiRNAs shared 11 nucleotides due to the conservative genomic termini and were likely generated from viral terminal panhandle structure, depending on both Dicer1 and Dicer2 in insects. In addition to targeting viral RNAs in a miRNA-like manner, the three vsiRNAs coordinately downregulated the expression of DOPA decarboxylase, thereby suppressing the prophenoloxidase immune reaction in insect vectors. In vsiRNA-silenced transgenic rice, the viral titer significantly decreased, indicating that these vsiRNAs promote RSV replication in rice. This study elucidates a unique function of vsiRNAs derived from the conserved panhandle structure of negative-strand RNA viruses in enhancing viral infection.